Study of Efficacy of Self Myofascial Release Technique on Text Neck Syndrome in Young Adults - Shinde, Pratiksha Ganpatrao; Bhat, Aaknansha (Journal of Neonatal Surgery, 2025)
Background: Text Neck Syndrome (TNS) is a growing musculoskeletal issue caused by prolonged forward head posture due to excessive smartphone use. It leads to symptoms such as neck pain, muscle stiffness, postural misalignment, and functional limitations. While various physiotherapy techniques have been studied for TNS, there is limited evidence on the effectiveness of Self-Myofascial Release (SMR) as a treatment. Methodology: A quasi-experimental study was conducted on 85 young adults (aged 18-25 years) diagnosed with TNS. Participants underwent a structured three-week SMR intervention using a tennis ball, targeting the trapezius and cervical muscles. Pre- and post-intervention assessments included the Numeric Pain Rating Scale (NPRS) for pain, Neck Disability Index (NDI) for functional limitations, and Craniovertebral Angle (CVA) for postural alignment. Statistical analysis was conducted using paired t-tests. Results: The study revealed significant improvements post-intervention. NPRS scores at rest decreased from 6.11 to 2.39 (p < 0.05), and during movement, from 8.07 to 3.85 (p < 0.05). NDI scores significantly reduced from 33.45 to 15.99 (p < 0.05), indicating improved functional ability. CVA improved from 44.55° to 48.56° (p < 0.05), suggesting enhanced postural alignment. Conclusion: Self-myofascial release is an effective, accessible, and cost-efficient intervention for managing TNS in young adults. It significantly reduces pain, improves functional ability and enhances postural alignment. Given the increasing prevalence of TNS, SMR can serve as a valuable self-management tool.